FAKTOR-FAKTOR YANG MEMENGARUHI MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN AKUNTANSI - Harsito, Wisnu Aji; ., Siswandari; Muchsini, Binti (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objective of this research is to investigate the factors influencing the entrepreneurial interest of the students of Study Program of Accounting Education. This research used the descriptive quantita-tive method. Its population was all of the students of Study Program of Accounting Education Depart-ment of the Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta. The sam-ples of research were determined through the purposive sampling technique. They consisted of 122 stu-dents of Classes 2013 and 2014. The data of research were analyzed by using the Exploratory Factor Analysis (EFA) as to investigate the factors influencing the entrepreneurial interest. The result of re-search shows that the factors influencing the entrepreneurial interest of the students of Study Program of Accounting Education include the following: (1) entrepreneurial competencies, namely: hard work, pe-severance and persistence, spirit at work, financial management abilities, leadership, business idea; (2) social environments, namely: occupations of people living surrounding the students, professions of col-leagues, parentsâ occupations, versatility to find opportunities; (3) positive perspectives toward the en-trepreneurial profession namely: perceptions on entrepreneurship, future goals or ambitions, work with-out time-bound, and work time without any interferences from others; (4) work flexibility and autonomy, namely: disliking being controlled, no intervention from others during work time, and freedom to earn income; (5) business capitals, namely: capital ownership, entrepreneurial program, and smartness in decision-making; (6) entrepreneurship education, namely: entrepreneurship course; and (7) personal background, namely: parentsâ occupations, capital ownership, and skills.Keywords: Social environments, profession, entrepreneurshipABSTRAKPenelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi minat berwirausaha mahasiswa Program Studi Pendidikan Akuntansi. Penelitian ini merupakan penelitian deskriptif kuantitatif. Populasi penelitian adalah seluruh mahasiswa Program Studi Pendidikan Akuntansi FKIP Universitas Sebelas Maret. Pengambilan sampel menggunakan teknik purposive sampling. Sampel penelitian adalah mahasiswa angkatan 2013 dan 2014 sebanyak 122 mahasiswa. Analisis data untuk mengetahui faktor-faktor yang memengaruhi minat berwirausaha menggunakan Exploratory Factor Analysis (EFA). Berdasarkan analisis data dan pembahasan, faktor-faktor yang memengaruhi minat berwirausaha mahasiswa antara lain (1) kompetensi wirausaha meliputi pekerja keras, tekun dan ulet, semangat kerja, kemampuan mengelola uang, jiwa kepemimpinan, ide bisnis, (2) lingkungan sosial meliputi pekerjaan masyarakat sekitar tempat tinggal, profesi teman, pekerjaan orang tua, pandai menemukan peluang, (3) pandangan positif terhadap profesi wirausaha meliputi persepsi terhadap wirausaha, cita-cita, pekerjaan tanpa terikat waktu, waktu kerja tanpa intervensi orang lain, (4) fleksibel dan kebebasan dalam bekerja meliputi tidak suka diatur, waktu kerja tanpa intervensi orang lain, kebebasan mencari pendapatan, (5) modal usaha meliputi kepemilikan modal, program kewirausahaan, pandai membuat keputusan, (6) pendidikan kewirausahaan yaitu mata kuliah kewirausahaan, (7) latar belakang pribadi meliputi pekerjaan orang tua, kepemilikan modal, keterampilan.Kata Kunci: lingkungan sosial, profesi, kewirausahaan